Exploring the binding dynamics of anticancer Dihydropyrimidinone derivatives with Serum Albumin: A multispectral approach - Chandraprakash Gond; Shivani Daksh; Akanksha Mishra; Nikhil Kumar; Anupama Datta; Anjani Kumar Tiwari (Chemical Physics Impact)
In this work, we have investigated the synthesis and characterization of two novel anticancer agents, 5-acetyl-6-methyl-4-phenyl-3,4-dihydropyrimidin-2(1H)-one (L1) and 2-Acetyl-4-(3,4-dimethoxy-phenyl)-6-methyl-3,4-dihydro-1H-pyrimidin-2-one (L2), utilizing the Biginelli reaction, which involves the cyclocondensation of urea, an aromatic aldehyde, and a β-ketoester. The structures of these compounds were confirmed through NMR and mass spectroscopy, revealing distinct molecular characteristics. Multi-spectroscopic methods, including UV–visible and fluorescence spectroscopy, demonstrated a static quenching mechanism with a drug-ligand linkage constant on the order of 10−5 M−1, indicating strong binding affinity to bovine serum albumin (BSA). The binding affinities of L1 and L2 to BSA were calculated with ΔG values of -5.68 and -5.48 kcal/mol, respectively, highlighting their potential for effective drug delivery. ADMET studies indicated favorable drug-like properties, including good gastrointestinal absorption and low toxicity profiles. Molecular docking studies identified critical interactions with BSA, particularly involving residues Trp134, Tyr139, and Phe133, which play significant roles in the binding process. These findings underscore the potential of L1 and L2 as promising candidates for anticancer therapy, supported by their robust interactions with serum albumin and favorable pharmacokinetic properties.